Home is where the heart is - Skulte-Ouaiss, Jennifer (2013)
In a country with a history of conflict, Lebanese not only have long sought emigration as a means of improving their safety and prosperity but also have sought out second passports as ‘safeguards’ to be used when things got rough at home. Little has been done on how Lebanese view these ‘second passports’ and the actual citizenship that comes with them. This article seeks to tackle this topic through analysing interviews of 10 Lebanese citizens who also hold European citizenship through naturalisation. How these Lebanese view their European citizenships will be described before turning to discussion of how this may affect the understandings of citizenship in Europe. The article concludes by looking on how the understandings of citizenship in liberal democracies in Europe on the part of citizens who normally reside outside of the state and who obtain citizenship as a ‘safety’ option may affect the broader understandings of citizenship in these countries.